2000
DOI: 10.1080/09540120050123774
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to antiretroviral medication adherence in HIV-infected women

Abstract: Little is known about the barriers which women living with HIV/AIDS encounter that impede their adherence to antiretroviral medication regimens. Yet in order to design effective interventions to improve women's adherence, it is first imperative to identify the factors that contribute to their non-adherence. The purpose of this study was to explore, from HIV-infected women's own perspectives, the barriers they faced in adhering to combination antiretroviral therapies. Twenty HIV-infected women were asked to kee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
1
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 0 publications
6
87
1
5
Order By: Relevance
“…These findings are generally consistent with several of the facilitators and barriers to, and strategies for adherence found in the literature on HIV treatment and other PrEP regimens. [21][22][23][24][25][26][27] Unique to participating in a blinded PrEP trial, participants clearly reported commitment to the study and the scientific question as motivators to take the study pills, linking agreement to participate in the study directly to agreement to take the study product daily. US MSM have been at the forefront of HIV/AIDS research and activism since the beginning of the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are generally consistent with several of the facilitators and barriers to, and strategies for adherence found in the literature on HIV treatment and other PrEP regimens. [21][22][23][24][25][26][27] Unique to participating in a blinded PrEP trial, participants clearly reported commitment to the study and the scientific question as motivators to take the study pills, linking agreement to participate in the study directly to agreement to take the study product daily. US MSM have been at the forefront of HIV/AIDS research and activism since the beginning of the epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Although further investigations are required to better characterize differences in discontinuation rates, factors such as pregnancy and differences in adherence 25,26 or safety profile 11,26 between sexes have been proposed as potential reasons to explain the increased rate of discontinuation observed in females.…”
Section: Jansen Et Almentioning
confidence: 99%
“…The practical barriers and psychological burden further complicate the administration of medications, which itself often serves as a painful reminder of the disease. 24 The global epidemic of HIV continues, with an increasing impact on children. By the end of 2004, an estimated 2.2 million children under 15 years of age worldwide were living with HIV; in that year alone, 640 000 were newly infected.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%